2010
DOI: 10.1007/s00405-010-1348-2
|View full text |Cite
|
Sign up to set email alerts
|

Is there a correlation between 18F-FDG-PET standardized uptake value, T-classification, histological grading and the anatomic subsites in newly diagnosed squamous cell carcinoma of the head and neck?

Abstract: Metabolic tumor activity correlates with T-stage of HNSCC. However, histological tumor grading does not correlate with SUV(max). The role of primary tumor SUV(max) as a predictor of outcome or survival remains unclear. Clinicians should therefore exercise caution in attributing any clinical importance to SUV(max) obtained from a single PET/CT exam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 20 publications
3
21
1
Order By: Relevance
“…Both the ADC values and the SUV values of HNSCC in the current study are similar to those reported by previous investigators [1315, 24, 29, 30, 4246]. In our study, there was no statistically significant association between the histologic tumour grade and SUV or ADC values (Table 5), although we observed a trend towards higher SUV and lower ADC values in poorly differentiated as compared to well differentiated HNSCC (Table 5).…”
Section: Discussionsupporting
confidence: 92%
“…Both the ADC values and the SUV values of HNSCC in the current study are similar to those reported by previous investigators [1315, 24, 29, 30, 4246]. In our study, there was no statistically significant association between the histologic tumour grade and SUV or ADC values (Table 5), although we observed a trend towards higher SUV and lower ADC values in poorly differentiated as compared to well differentiated HNSCC (Table 5).…”
Section: Discussionsupporting
confidence: 92%
“…SUV max was significantly higher in T3-4 than T1-2, but not associated with histologic grade like previous reports about FDG uptake and T stage, 6,13-16 and histologic grade. 13,14 Although in our study, the higher tendency of SUV max in N1-3 did not reach the statistically significant level, it was reported to be significantly higher in N1-3 than N0 15 and N2-3 than N0 -1. 16 We used ADC calculated from b values of 0 and 800 seconds/ mm 2 .…”
Section: Discussioncontrasting
confidence: 81%
“…It is essential to identify such tools for a homogenous group of tumor sites and histological diagnosis; else, the use of general delineating tool might be erroneous. In an attempt to study the impact of histological diagnosis and subsites on FDG PET, Haerle et al 17 have studied 18 F-FDG-PET SUV in patients with head and neck carcinoma and found no statistically significant correlation between the different anatomical subsites and SUV max . There was no significant correlation between SUV max and tumor grading after adjusting for T stage and anatomical localization of the tumor in head and neck cancers.…”
Section: Discussionmentioning
confidence: 99%